Application of the Economic Order Quantity (EOQ) Method in Soybean Raw Material Inventory Control at the Haji Maman Tofu Factory in Matraman District, East Jakarta - Al Firdausi, Achmad Rizal; Suprayitno, Degdo (Yayasan Sinergi Kawula Muda, 2023)
This research is based on the lack of implementation of a method in controlling the inventory of soybean raw materials at Haji Maman’s Tofu Factory in the Matraman District of East Jakarta. Haji Maman’s Tofu Factory stil relies on daily records and sometimes uses estimates or assumption in its operational activities. In the procurement of raw materials, there is often an excess due to the lack of precise calculations regarding the ordering needs of raw materials, resulting in accumulation in the warehouse. In this study, the researcher utilized the Economic Order Quantity (EOQ) method, which determines the optimal quantity of raw material orders for each purchase, the optimal purchase frequency, and establishes the Re-Order Point. The approach and type of research used is a quantitative research method with a descriptive research approach. The objective of this study is to examine the implementation of the EOQ method in controlling the inventory of soybean raw materials at Haji Maman’s Tofu Factory in the Matraman District of East Jakarta. Data Collection was conducted through observation and interviews with Mr. Haji Maman, the owner. The data analysis technique employed was the EOQ method, taking into account purchase frequency, Re-Order Point, and Total Inventory Cost (TIC). The results of this study indicate that the optimal average frequency of raw material orders is 17 times per year. The total inventory cont using Haji Maman’s Tofu Factory policy amounts to Rp. 9,709,261, while using the EOQ method it amounts to Rp. 7,492,129, resulting in savings of Rp. 2,217,132 for Haji Maman’s Tofu Factory. The Re-Order Point is determined to be 216 kilograms.